Cuidado de enfermería de la corporeidad del cliente de terapia intensiva - May Uitz, Saúl (2016)
The present investigation Qualitative, descriptive, was conducted to describe and analyze the nursing care of the customer corporeality intensive care regional hospitals in Mérida, Yucatán, México. The theory underlying the study is Maturana and Figueiredo. The study was, involving ten nurses, seven females and three males, intensive care specialists, determining participants was by theoretical saturation. A semi-structured interview and participant observation was used for data collection, speeches were analyzed through content analysis, bearing in mind the criteria of rigor and ethics. The analysis of the speeches originated three empirical categories, which are: Caring corporeality, with the corpo three subcategories caring, taking care of me in the other and languaging care. Therapeutic care; two categories; caring and caring with coupling technology with soft technology and Extension of care; with two subcategories, taking care with family and caring with music therapy. Conclusion. Corporeality customer care in the intensive therapy is to understand that not only takes care of the physical body but also the spiritual, spirituality involves the process of caring for oneself and others, languaging care; It is a presence for the presence caresses and listen, watch what therapeutic and technological coupling allows the nurse to use her body as an instrument of care and other elements such as music therapy, allowing the family as an extension of care.